2016
DOI: 10.1080/1120009x.2016.1245174
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetically-based prediction of the effects of antibiotic combinations on resistant Staphylococcus aureus mutants: in vitro model studies with linezolid and rifampicin

Abstract: To explore if combinations of linezolid (L) with rifampicin (R) are able to restrict Staphylococcus aureus resistance, the enrichment of L- and R-resistant mutants was studied in an in vitro dynamic model. L- and R-resistant mutants were enriched in all single drug treatments. In contrast, L-resistant mutants were not enriched and R-resistant mutants were similar to baseline amounts with only minimal regrowth at the end of the combination treatments. These effects appear to be explained by lowering the mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…1a–c , and Tables 1 and 2 roughly showed that the remarkable the synergistic effect is, the narrower their MSWs are, and the wider the ratio range of two agents in a synergistic combination closing each other’s MSW. Thereby, the indifferent combination can prevent resistance by applying the same doses as they administrated alone or by increasing their doses 26 , while antimicrobial combination with FICIs as small as possible had greater and superior potency to effectively prevent resistance, which was also proved by previous paper 30 . Another, to reveal changes in susceptibility after treatment, the MIC of an antimicrobial agent against exposed bacterial colony was determined for accessing the effectiveness to prevent resistance, while no paper involved whether the MPC of that changes.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…1a–c , and Tables 1 and 2 roughly showed that the remarkable the synergistic effect is, the narrower their MSWs are, and the wider the ratio range of two agents in a synergistic combination closing each other’s MSW. Thereby, the indifferent combination can prevent resistance by applying the same doses as they administrated alone or by increasing their doses 26 , while antimicrobial combination with FICIs as small as possible had greater and superior potency to effectively prevent resistance, which was also proved by previous paper 30 . Another, to reveal changes in susceptibility after treatment, the MIC of an antimicrobial agent against exposed bacterial colony was determined for accessing the effectiveness to prevent resistance, while no paper involved whether the MPC of that changes.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, human body is a complex system, and the antimicrobial and resistance-prevented effects were influenced by various factors including human body (defense system and microorganism communities), antimicrobial agents (drug concentrations in blood and infection site, pharmacokinetics, toxic side effect to human body including immune suppression, and selective antimicrobial or bactericidal effect to destruct the balance of microorganism communities which were favorable to prevent infection and resistance) and pathogenic bacteria (biofilm, persisters, and resistant mutants). Although synergistic combination RM/DC theoretically had a great potency to prevent resistance of two isolates MRSA 01 and 02 in a wide proportionality range, the actual effect preventing resistance of combination RM/DC with different proportions needs to be further verified using pharmacokinetic simulations on in vitro model and those of bacterial biofilm 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, a wide range of studies have been conducted to elucidate the effects of single as well as multiple drugs on bacterial evolution. In vitro pharmacokinetic/pharmacodynamic studies have identified optimal dosing regimens using multiple drugs that can effectively suppress bacterial growth and prevent the emergence of drug-resistant mutants 3 4 5 6 . Laboratory evolution studies utilising whole-genome sequencing 7 8 9 10 11 12 and transcriptome analysis 13 14 have been applied to investigate longer-term dynamics of bacterial adaptation to stressful drug environments, and provide insight to the complex relationships between drug resistance, and genetic alterations and gene expression changes.…”
mentioning
confidence: 99%
“…The daptomycin-to-gentamicin concentration ratios, at which MPCs of antibiotics were determined, were equal to the respective daptomycin-to-gentamicin AUC ratios used in the pharmacokinetic simulations. This pharmacokinetic-based approach to MPC determination has been used in previous studies with the following antibiotic combinations: linezolid-rifampicin [18], daptomycinrifampicin [19], linezolid-gentamicin [17] and linezolid-daptomycin [16]. In the current study the increased T >MPC s for each antibacterial in the presence of the second agent were consistent with enhanced anti-mutant effects of daptomycin and gentamicin in combination and consequently with decreased areas under the bacterial mutant concentration-time curve (AUBC M s) of daptomycin (AUBC M(D) ) and gentamicin (AUBC M(G) ), respectively.…”
Section: Discussionmentioning
confidence: 99%